La selección artificial en el origen del pensamiento evolutivo y en los procesos de domesticación en el mundo actual - Arturo Argueta Villamar; Ricardo Noguera Solano; Eduardo Corona-M. (Revue d'ethnoécologie)
Domestication of organisms is a set of knowledge and practices that have generated, throughout history, knowledge and procedures, and new lineages or populations. Knowledge obtained from these processes, particularly those related to biological variation and population diversification, became a key element in the origin of Lamarckian and Darwinian evolutionary thought, not only in the sense of evidencing the diversification of domesticated species and the effect of species transformation, but also in the development of the scientific explanation of evolution. That is, to base the rational application of knowledge about domestication in discussions on transformation, indirect evidence, working hypotheses and the rethorical figure from which the concept of natural selection was built. Ideas about the variation of plants and animals in a domestic state defined the meaning of the ideas of biological variation, descent with modification and common ancestry. In broader terms, it was crucial to give an epistemically radical meaning to the knowledge obtained in the practices that human beings have carried out for thousands of years, to understand what nature has done for millions of years. New and recent analyses, obtained from archaeological, anthropological, ethnoecological and ethnobiological studies, show that domestication processes continue with great vigor today, based on traditional knowledge accumulated by millions of peasant and pastoral communities in the contemporary world. This knowledge is highly relevant for the conservation of biodiversity and agrobiodiversity, the use of natural resources, biocultural heritage and the sustainable future of the planet.